Blue eyes, brown eyes : a cautionary tale of race and brutality - Bloom, Stephen G. (University of California Press, 2021)
"The day after Martin Luther King, Jr.'s assassination, Jane Elliott, a third-grade schoolteacher in rural Iowa, tried out a shocking experiment to show the scorching impact of racism on children. Elliott separated her students according to the color of their. Those with brown eyes would lord over those with blue eyes. The brown-eyed students were given permission to heckle and berate the blue-eyed students, even to start fights with them. The Blue-Eyed, Brown-Eyed Experiment would become world famous. Elliott would go on to appear on Johnny Carson's Tonight Show, followed by a stormy White House conference, and tens of thousands of media events and diversity training sessions around the world. Elliott taught "Black Lives Matter" fifty years before the phrase was ever uttered. Yet the small town where Elliott began the incendiary experiment never forgot or forgave her. She paid a price for her hard-fought fame. But was Elliott the benign and enlightened mother of diversity she claimed to be? The damage she caused still reverberates. An indelible, confounding portrait of a woman driven to succeed, set against the backdrop of a proud and upright farming community"--